The Water cycle - Trueit, Trudi Strain (New York : Scholastic, 2002)
Perfectly suited for today's science curriculum, this series explores aspects of the wonders of earth science. Each book fully explains complex concepts such as erosion, the water cycle, and evaporation. The books also highlight the human side of science by discussing the techniques and lives of people who study the Earth--meteorologists, storm chasers, geologists, and more.